A literatura como lugar de memória: uma análise da obra “a máquina de fazer espanhóis,” de Valter Hugo Mãe - PANTOJA, Edirlene Costa (2020)
In the Spanish making machine, the narrative is constructed from the point of view of the narrator, António Jorge Silva, at the moment when he is abandoned by his children after his wife's death. In order to preserve identity, the old man begins to narrate his memories and listen to the memories of other old men who are in the asylum in the same situation as he, the other "Silvas". Thus, this paper aims to analyze the role of memory in the novel the machine to make Spaniards of Valter Hugo Mãe. To do so, we start with the following research question: to what extent individual memory reflects in a set of collective memories of experiences of the elderly in the home? To answer this question, we carried out a research whose general objective is: to analyze the role of memory in the narrative of Valter Hugo Mãe's Spanish making machine, and its specific objectives: to identify the role of individual memory; establish the interrelationship between individual memory and collective memory; to point the confluence between individual and collective memory for the reconstruction of a past common to the characters of the novel. This research is based on Benjamin (1987), Derrida (1997), Derrida (2001), Freud (1976), Halbwachs (2003) and Ricouer (2007). The methodological approach used in the research was of bibliographic character. The analysis points to the memory, in the narrative of fiction, as a fundamental element for the understanding of a collective past.